Factors influencing information technology usage among managerial employees :a case study in A5-Star Hotel in Petaling Jaya, Selangor Darul Ehsan - Benedict, Gareth (University Malaysia Sarawak (UNIMAS), 2002)
This study is done to determine the factors influencing I.T usage among managerial employees of Hilton Petaling Jaya, Selangor Darul Ehsan.